Integrated agricultural research for development ...from concept to practice - Adewale, A.A.; Pluwole FA; Buruchara, Robin Arani; Nyamwaro, Sospeter S. (Forum for Agricultural Research in Africa, 2013)
This publication presents a synthesis of methods and lessons learnt in the implementation of the Integrated Agricultural Research for Development (IAR4D) concept within the Sub-Saharan Africa Challenge Program (SSA CP). It relates lessons learnt and impact gained from the program between 2005 to 2010. The SSA CP is the only Challenge program of the Consultative Group on International Agricultural Research (CGIAR) program that is targeted at a particular region and it represents an important partnership between the stakeholders in African Agriculture, represented by FARA, and the CGIAR. The IAR4D concept utilizes the principles of innovation systems approach to foster significant changes in agriculture through wholesome engagement of stakeholders in useful partnership, market integration and participatory innovation along technological, institutional and infrastructural realm.